Knowledge, democracy and action : Community-university research partnerships in global perspectives - Fontan, Jean-Marc; Lall, Nirmala; Tandon, Rajesh; Jackson, Edward T., 1951-; Hall, Budd L. (Universities and lifelong learning series., 2013)
Knowledge, democracy and action: Community-university research partnerships in global perspectives is based on a three-year international comparative study undertaken by the Global Alliance on Community Based Research and supported by the UNESCO Chair in Community Based Research and Social Responsibility in Higher Education. It provides evidence from twenty case studies around the world on the power and potential of community and higher education based scholars and activists working together in the co-creation of transformative knowledge. The book draws on the experience and insights of thirty-seven scholars and practitioners from the Global South and North. Opening with a theoretical overview of knowledge, democracy and action, the book is followed by analytical chapters providing lessons learned and capacity building in the north and the south, on the theory and practice of community university research partnerships, models of evaluation, approaches to measuring the impact and an agenda for future research and policy recommendations.